The Credibility of the Church Based on Benevolence in the Light of the Works of Marian Rusecki - Mastej, Jacenty (Verbum Vitae, 2023)
The problem addressed in the article is the question of the credibility of the Church based on benevolence in the light of the work of Marian Rusecki. The present issue was addressed and resolved in three stages. In the first stage – invoking the Ecclesia-forming activity of Jesus – the benevolence-based aspects related to the genesis of the Church were pointed out. In the second stage, the benevolent identity of the Ecclesia was presented, for which well-being is an essential part of its life and mission. At the final stage, the matter of recognizing the benevolence-based credibility of the Church was addressed, taking into account Rusecki’s personalistic and sign-based concept of the Church and the signs of its credibility. Elements that are helpful in recognizing the benevolence-based credibility of the Church were also identified. The Church’s benevolence – which is rooted in the life and work of Jesus – is clear in its connection to the entirety of human life. Goodness is the overriding value that man needs in life, especially in illness, suffering or misfortune. The Ecclesia is a clear and credible sign of God’s goodness when, aware of the salvific goods which it has received from Christ, it bestows them on human beings, remaining particularly sensitive to human injustice and evil, and takes the side of the disadvantaged and the suffering, providing them with concrete help, both spiritual and material.